EFFICACY OF AVIAN INFLUENZA VIRUS LOCALLY MANUFACTURED AND IMPORTED VACCINES - T. M. Shaukat; M. A. Muneer; M.U. D. Ahmad; A. Maqbool; T. M. Shaukat (Journal of Animal and Plant Sciences, 2016)
Monovalent H7 and H9 inactivated Avian Influenza Virus (AIV) vaccines were developed and its efficacy was compared with the locally available and imported vaccines including monovalent (Flu-Vac H7, Gallimune H9) and bivalent (Avi-Flu H7+H9, Otto-flu H7+H9) using inoculation in five broiler breeder flocks under field conditions. The sero conversion in the inoculates was studied using haemagglutination inhibition (HI) test. On day 21 post-vaccination; in case of H7N3 virus vaccines, the antibody titer; the Geometric Mean (GM) HI titer recorded were as 55.7 in group A (the group inoculated with Gallimmune; Merial vaccine) chickens, 52.0 in group B (the group inoculated with locallly manufactured Avi-Flu vaccine) 59.7 in group C (the group inoculated with locally manufactured Otto-Flu vaccine), 29.9 in group D (the group inoculated with newly developed local vaccine) and 2.5 in group E (un-inoculated control group). In case of H9N2 virus vaccines, on day 21 post vaccination, the GM HI titers of chicks in group A, B, C, D and E were recorded as 27.9, 68.6, 64.0, 24.3 and 2.5, respectively. This study indicated that the locally prepared AI vaccines also provoked quite good HI antibody titers in poultry flocks in Pakistan.
Keywords: Avian Influenza; vaccine preparation; vaccine efficacy comparison